(untitled) (Educação e Pesquisa, 2019)
Discussions on racial inequalities in the access to higher education have promoted, since the last decade, the adoption of affirmative action policies aimed at correcting historical disparities, such as the Federal Law of Quotas (Act No. 12.711/2012). However, in spite of its importance, this policy still lacks mechanisms for monitoring and evaluation, given that one of the potentially most useful surveys for that – the Census of Higher Education (CES, in Portuguese) – presents high rates of non-racial statement, due to the missing values of the color/race item reported by the Federal Higher Education Institutions (IFES, in Portuguese). Intending to enhance the monitoring process of this legislation, this study made use of the incoming undergraduate students databases of the IFES at the CES, from 2012 through 2015, in order to, by merging them with the National High School Exam (ENEM, in Portuguese) datasets, search for the color/race information self-ascribed by the same individuals when they signed up for the exam, and thus take their respective racial statements in ENEM with the purpose of increasing the racial statement rate in the Census. Among 2015 students, this procedure has increased racial statement from 75.9 percent to 96.4 percent. In addition, I analyze the results obtained according to the combinations formed by Institution-Course-Shift, considered as the reference unit of the Law of Quotas, and conclusion is that this operation, not only adds up few biases in the racial composition of the students but it can also be considered a valid strategy to enhance the monitoring of such policy as long as high rates of racial underreporting persist.